2022
DOI: 10.1093/ehjacc/zuac135
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal cardiopulmonary resuscitation: a national study on the association between favourable neurological status and biomarkers of hypoperfusion, inflammation, and organ injury

Abstract: Background In refractory out-of-hospital cardiac arrest (OHCA) with prolonged whole-body ischemia, global tissue injury proceeds even after establishment of circulation with extracorporeal cardiopulmonary resuscitation (ECPR). We aimed to investigate the role of biomarkers reflecting hypoperfusion, inflammation, and organ injury in prognostication of patients with refractory OHCA managed with ECPR. Methods This nationwide ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Three studies demonstrated an association of higher CRP levels at admission with mortality but no independent association in multivariable model (not tested in two and not significant in the third), 25,33,42 and two found no difference between neurological outcome groups 21,46 . Gregers et al reported that lower CRP levels at admission and on day one independently predict poor neurological outcome at hospital discharge in a study where all patients underwent extracorporeal cardiopulmonary resuscitation 45 . Studies on later time points reported conflicting results: Kim et al reported unadjusted association with outcome on days one to three, 44 Andersson et al on day one, 20 Chong et al and Kim et al on day three and Ristagno et al an independent association on day two, 16,48,49 whereas three studies found no association at any time point 12,13,19,47 .…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Three studies demonstrated an association of higher CRP levels at admission with mortality but no independent association in multivariable model (not tested in two and not significant in the third), 25,33,42 and two found no difference between neurological outcome groups 21,46 . Gregers et al reported that lower CRP levels at admission and on day one independently predict poor neurological outcome at hospital discharge in a study where all patients underwent extracorporeal cardiopulmonary resuscitation 45 . Studies on later time points reported conflicting results: Kim et al reported unadjusted association with outcome on days one to three, 44 Andersson et al on day one, 20 Chong et al and Kim et al on day three and Ristagno et al an independent association on day two, 16,48,49 whereas three studies found no association at any time point 12,13,19,47 .…”
Section: Resultsmentioning
confidence: 98%
“…We found no studies focusing primarily on WBC as a marker after OHCA. Three studies reported independent prognostic value; lower WBC at admission was associated with poor neurological outcome at hospital discharge in a study where all patients underwent extracorporeal cardiopulmonary resuscitation, 45 and higher WBC and neutrophils on day one were associated with poor six‐month neurological outcome in another study 46 . Higher WBC on day one independently predicted poor neurological outcome at hospital discharge 51 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations